2023
DOI: 10.2807/1560-7917.es.2023.28.11.2200543
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal spread of tick-borne encephalitis in the EU/EEA, 2012 to 2020

Abstract: Background Tick-borne encephalitis (TBE) is a vaccine-preventable disease involving the central nervous system. TBE became a notifiable disease on the EU/EEA level in 2012. Aim We aimed to provide an updated epidemiological assessment of TBE in the EU/EEA, focusing on spatiotemporal changes. Methods We performed a descriptive analysis of case characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
(48 reference statements)
2
12
0
Order By: Relevance
“…In a large European study that included the period from 2012 to 2020, 19 countries reported 24,974 TBE cases. Lithuania, Latvia, and Estonia had the highest reporting rates [ 1 ]. The continuing increase in the number of TBEV strains detected in I. ricinus in Europe and the westward spread of I. persulcatus and the more virulent TBEV European and Siberian strains is of great concern [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large European study that included the period from 2012 to 2020, 19 countries reported 24,974 TBE cases. Lithuania, Latvia, and Estonia had the highest reporting rates [ 1 ]. The continuing increase in the number of TBEV strains detected in I. ricinus in Europe and the westward spread of I. persulcatus and the more virulent TBEV European and Siberian strains is of great concern [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tick-borne diseases are becoming an increasing public health problem. Tick-borne encephalitis (TBE) is the most widespread tick-borne viral disease in the Euro-Asia region and the second most common tick-transmitted disease in Europe [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years however there has been an increase in cases. [26][27][28] The rise in TBE cases is mainly due to environmental, ecological, and socioeconomic factors that increase the risk of human exposure to infected ticks. 29,30…”
Section: Epidemiology Of Tick-borne Encephalitis Virusmentioning
confidence: 99%
“…One unique example when it comes to the change of cases is Austria, where for a long time the number of cases remained constant for a long time. In the recent years however there has been an increase in cases 26–28 . The rise in TBE cases is mainly due to environmental, ecological, and socioeconomic factors that increase the risk of human exposure to infected ticks 29,30 …”
Section: Epidemiology Of Tick‐borne Encephalitis Virusmentioning
confidence: 99%